2018
DOI: 10.1007/s12035-018-1212-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin Expression in the Brain: a Story of Tissue Homeostasis Preservation

Abstract: After its discovery in 2000, the notion grew that neuroglobin, a neuronal specific heme protein, is involved in cytoprotection. To date, neuroglobin levels have been positively correlated with a beneficial outcome in a plethora of neurotoxic insults, e.g., ischemic and traumatic brain injuries and Alzheimer's disease. The first part of this review goes further into these changes of neuroglobin expression upon different neuronal insults as well as the underlying regulation. In the second part, we shed light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 181 publications
1
24
0
Order By: Relevance
“…Neuroglobin is a specific oxygen-binding globin protein first discovered in 2000 that has been verified to play an endogenous neuroprotective molecule against ischemia, hypoxia, oxidative stress damage, and related neurological disorders (Burmester et al, 2000; Qiu and Chen, 2014; Nair et al, 2018; Van Acker et al, 2018). Several studies have demonstrated that Ngb reduces ROS generation, preserves mitochondrial ATP production, resets the level of mitochondrial cytochrome c , participates in mitochondrial-mediated cell death signaling, and acts as a regulator of signal transduction in the brain (Wakasugi et al, 2005; Yu et al, 2009; Antao et al, 2010; Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroglobin is a specific oxygen-binding globin protein first discovered in 2000 that has been verified to play an endogenous neuroprotective molecule against ischemia, hypoxia, oxidative stress damage, and related neurological disorders (Burmester et al, 2000; Qiu and Chen, 2014; Nair et al, 2018; Van Acker et al, 2018). Several studies have demonstrated that Ngb reduces ROS generation, preserves mitochondrial ATP production, resets the level of mitochondrial cytochrome c , participates in mitochondrial-mediated cell death signaling, and acts as a regulator of signal transduction in the brain (Wakasugi et al, 2005; Yu et al, 2009; Antao et al, 2010; Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ngb is a monomeric protein that reversibly binds oxygen with a reported P 50 ranging from 0.9 to 10 torr and displays a hexa-coordinated scheme [ 70 , 206 , 207 ]. Initially identified in rodent and human brain tissues [ 70 ], Ngb is expressed in the central (olfactory bulb, solitary tract nucleus, cerebellum, amygdala, hippocampus, thalamus and grey substance of spinal cord) and peripheral (sensory and autonomic ganglia) nervous system, with particularly high expression in the hypothalamus, in astrocytes, but also in the gastrointestinal tract, in endocrine tissues such as the pituitary gland, adrenal glands and islets of Langerhans, in the photoreceptor inner segments of the retina, retinal pigment epithelium, inner and outer plexiform layers, the retinal ganglion cell layer, inner and outer nuclear layers, and the optic nerve, as well as in the heart and testes [ [208] , [209] , [210] , [211] , [212] ] ( Fig. 3 ).…”
Section: Neuroglobinmentioning
confidence: 99%
“…With regard to intact RBCs, erythrophagocytosis by microglia [105] is usually insufficient to prevent free hemoglobin release and neurotoxicity. Similar to myoglobin in muscles, neuroglobin is a reserve form of hemoprotein able to store oxygen and protect the brain, at least in part, from hypoxic/ischemic insults [106]. Ferroptosis also plays a role in secondary cell death in hemorrhagic stroke [107,108] and selenium loading can partially prevent ferroptosis in experimental strokes [109].…”
Section: Strokementioning
confidence: 99%